SPE/IADC Middle East Drilling Technology Conference and Exhibition 2011
DOI: 10.2118/145562-ms
|View full text |Cite
|
Sign up to set email alerts
|

Life Without Barite: Ten Years of Drilling Deep HPHT Gas Wells With Cesium Formate Brine

Abstract: The tradition of using barite to increase the weight of drilling fluids dates back to the early-1920's and, while it has been of great benefit to the oil industry over the past 90 years, it has also caused some chronic and persistent well construction problems along the way. These problems, which are very familiar to drillers, include well control difficulties, stuck pipe incidents and formation damage.The oil industry has known since the 1970's that replacing barite with suitable non-damaging solutes in reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…This problem results from loss circulation, torque and drag, equivalent circulation density (ECD) fluctuations, and also due to operation that requires drilling fluid to be static for long time. Downs et al [95] have observed that high loading of barite in typical drilling fluids increase frictional pressure losses when circulating in long sections, leading to unacceptably high ECD in narrow operating drilling windows (where pore pressures and fracture pressures are very close to each other). The solids-carrying function of conventional drilling fluid can be deteriorated, triggering dynamic and static barite sag, and intensifying the risk of losing well control in the case of high angle wells.…”
Section: Hpht Drilling Fluid Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem results from loss circulation, torque and drag, equivalent circulation density (ECD) fluctuations, and also due to operation that requires drilling fluid to be static for long time. Downs et al [95] have observed that high loading of barite in typical drilling fluids increase frictional pressure losses when circulating in long sections, leading to unacceptably high ECD in narrow operating drilling windows (where pore pressures and fracture pressures are very close to each other). The solids-carrying function of conventional drilling fluid can be deteriorated, triggering dynamic and static barite sag, and intensifying the risk of losing well control in the case of high angle wells.…”
Section: Hpht Drilling Fluid Challengesmentioning
confidence: 99%
“…Oil-based drilling fluid is normally chosen for HPHT drilling as a means of tackling high temperature conditions because it is stable to at least 450 • F in 16-h laboratory tests [101], it typically exhibits a lower coefficient of friction, and it provides a thinner and more lubricious filter cake [102]. Some drawbacks of OBDF are: (1) high cost, (2) influence on logging interpretation, (3) OBDF can absorb a large amount of gas, (4) environmental issues, and (5) the thermal expansion of OBDF is higher than WBDF, which can lead to pressurization of the annulus [95,101]. For example, invert emulsion system drilling fluid is environmental friendly and it has better thermal stability (up to 478 K); thus, it can be used to drill HPHT wells [103].…”
Section: Selection Of Hpht Base Drilling Fluidmentioning
confidence: 99%
“…The third technique used, microCT, is a relatively recent addition to formation-damage evaluation. It provides much greater resolution when compared to CT scanning and allows a 3D visualization of the pore structure, such that any changes occurring after testing could be detected by the density contrast (Green et al 2013). …”
Section: Corefloodingmentioning
confidence: 99%
“…Formate brines have been used over a number of years as drilling-and-completion fluids for HP/HT fields (Howard 1995;Bungert et al 2000;Saasen 2002;Simpson et al 2005;Oswald et al 2006;Berg et al 2009;Qureshi et al 2008;Downs 2011;Olsvik et al 2013). Olsvik et al (2013) summarized the results from eight HP/HT fields in which cesium formate was used as the completion fluid in conjunction with a cesium-formate drilling fluid or oil-based mud.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 18 years formate brines have been used as reservoir drill-in and completion fluids in more than 40 HPHT gas condensate field developments, accessing some of the deepest, hottest and highest-pressured reservoirs in Europe [Downs, 2010;Downs, 2011]. The UK and Norwegian governments publish monthly updated figures for the gas and condensate production from fields in their sectors of the North Sea.…”
Section: Introductionmentioning
confidence: 99%